Beta-catenin versus the other catenins: assessing our current view of canonical Wnt signaling - Miller, Rachel K. (2013)
The prevailing view of canonical Wnt signaling emphasizes the role of beta-catenin acting downstream of Wnt activation to regulate transcriptional activity. However, emerging evidence indicates that other catenins in vertebrates, such as members of the p120 subfamily, convey parallel signals to the nucleus downstream of canonical Wnt pathway activation. Their study is thus needed to appreciate the networked mechanisms of canonical Wnt pathway transduction, especially as they may assist in generating the diversity of Wnt effects observed in development and disease. In this chapter, we outline evidence of direct canonical Wnt effects on p120-subfamily members in vertebrates, and speculate upon these catenins’ roles in conjunction with or aside from beta-catenin.